Direct Binding of Three Tight Junction-Associated Maguks, Zo-1, Zo-2, and Zo-3, with the Cooh Termini of Claudins - Itoh, Masahiko (The Rockefeller University Press, 1999)
ZO-1, ZO-2, and ZO-3, which contain three PDZ domains (PDZ1 to -3), are concentrated at tight junctions (TJs) in epithelial cells. TJ strands are mainly composed of two distinct types of four-transmembrane proteins, occludin, and claudins, between which occludin was reported to directly bind to ZO-1/ZO-2/ZO-3. However, in occludin-deficient intestinal epithelial cells, ZO-1/ZO-2/ZO-3 were still recruited to TJs. We then examined the possible interactions between ZO-1/ZO-2/ZO-3 and claudins. ZO-1, ZO-2, and ZO-3 bound to the COOH-terminal YV sequence of claudin-1 to -8 through their PDZ1 domains in vitro. Then, claudin-1 or -2 was transfected into L fibroblasts, which express ZO-1 but not ZO-2 or ZO-3. Claudin-1 and -2 were concentrated at cell–cell borders in an elaborate network pattern, to which endogenous ZO-1 was recruited. When ZO-2 or ZO-3 were further transfected, both were recruited to the claudin-based networks together with endogenous ZO-1. Detailed analyses showed that ZO-2 and ZO-3 are recruited to the claudin-based networks through PDZ2 (ZO-2 or ZO-3)/PDZ2 (endogenous ZO-1) and PDZ1 (ZO-2 or ZO-3)/COOH-terminal YV (claudins) interactions. In good agreement, PDZ1 and PDZ2 domains of ZO-1/ZO-2/ZO-3 were also recruited to claudin-based TJs, when introduced into cultured epithelial cells. The possible molecular architecture of TJ plaque structures is discussed.